Proteome Analysis of the Gametophytes of a Western Himalayan Fern Diplazium maximum Reveals Their Adaptive Responses to Changes in Their Micro-Environment - Sareen, Bhuvnesh; Thapa, Pooja; Joshi, Robin; Bhattacharya, Amita (Frontiers in Plant Science, 2019)
Ferns have survived changing habitats and environmental extremes of different eras, wherein, the exploratory haploid gametophytes are believed to have played a major role. Therefore, the proteome of in vitro grown gametophytes of a temperate Himalayan fern, Diplazium maximum in response to 0 (G0), 1 (G1) and 3 % (G3) sucrose was studied. A total of 110 differentially expressed abundant protein spots were obtained. Among these, only 68 could be functionally categorized as unique proteins involved in various metabolic processes. Calcium dependent proteins-, receptor like kinases, G proteins, proteins related to of hormones hormonal signaling and their interaction with other pathways and cross-talk, and regulatory proteins were recorded indicating the involvement of five different signaling pathways. DEPs DAPs involved in the activation of genes and transcription factors of signaling and transduction pathways, transport and ion channels, cell-wall and structural proteins, defence, chaperons, energy metabolism, protein synthesis, modification and turnover were identified. The gametophytes responded to changes in their micro-environment. There was also significant increase in prothallus biomass and conversion of 2-dimensional prothalli into 3-dimensional prothallus clumps at 3 % sucrose. The 3-D clumps had higher photosynthetic surface area and also closer proximity for sexual reproduction and sporophyte formation. Highest accumulation of proline, enhanced scavenging of ROS and up-regulated DEPs DAPs of mostly, abiotic stress tolerance, secondary metabolite synthesis and detoxification at 3% sucrose indicated an adaptive response of gametophytes. Protein Protein Interaction network and Principal Component analyses, and qRT-PCR validation of genes encoding 12 proteins of various metabolic processes also indicated differential adjustment of gametophytes to different levels of sucrose in the culture medium. Therefore, a hypothetical mechanism was proposed to show that even slight changes in the micro-environment of D. maximum gametophytes triggered multiple mechanisms of adaptation. Many DEPs DAPs identified in the study have potential use in crop improvement and metabolic engineering programs, phytoremediation and environmental protection.